FAKTOR PENENTU DARI PERSEPSI NILAI PELANGGAN DAN IMPLIKASINYA TERHADAP INTENSI PEMBELIAN - Anotonius Agus Susanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
The purpose of this study is to examine the determinants of customer value perception of the purchase intention on the internet consumer services. The methodology of this research was hypothesis testing. Sample in this research is conducted by non-probability method with purposive sampling technique from350 internet subscribers in Jakarta. The result of the research by structural equation modeling analysis in the first model showed that the service quality, experience economy and price fairness have a significant influence to customer value perception. In the second model, the results showed that service quality, experience economic, price fairness and customer value perception have a significant influenceto purchase intention.